2010
DOI: 10.1093/nar/gkq712
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the nuclear matrix-bound chromatin hubs by a new M3C experimental procedure

Abstract: We have developed an experimental procedure to analyze the spatial proximity of nuclear matrix-bound DNA fragments. This protocol, referred to as Matrix 3C (M3C), includes a high salt extraction of nuclei, the removal of distal parts of unfolded DNA loops using restriction enzyme treatment, ligation of the nuclear matrix-bound DNA fragments and a subsequent analysis of ligation frequencies. Using the M3C procedure, we have demonstrated that CpG islands of at least three housekeeping genes that surround the chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 58 publications
0
16
0
1
Order By: Relevance
“…The mechanisms driving such interactions have only recently begun to be uncovered as new techniques, such as chromosomal conformation and capture (3C), have evolved. A subset of these interactions corresponds to nuclear matrix attachment regions, as recently demonstrated by 3C experiments [22]. Thus, a better understanding of nuclear scaffold/matrix localization of cis-elements and their regulatory proteins are needed.…”
Section: Introductionmentioning
confidence: 84%
“…The mechanisms driving such interactions have only recently begun to be uncovered as new techniques, such as chromosomal conformation and capture (3C), have evolved. A subset of these interactions corresponds to nuclear matrix attachment regions, as recently demonstrated by 3C experiments [22]. Thus, a better understanding of nuclear scaffold/matrix localization of cis-elements and their regulatory proteins are needed.…”
Section: Introductionmentioning
confidence: 84%
“…However, its protein content largely overlaps with that of the nucleoskeleton, a well-defined, intermediate filament-based protein network of the nucleus (44). Moreover, the DNA content of the nuclear matrix represents a fraction of the genome, which is resistant to extensive DNase I digestion, and specific sequences that are enriched in this fraction possess gene regulatory functions (7,45). As active, open chromatin structures are highly accessible to nucleases (46) and active rDNA is largely nucleosome-depleted (47), we suppose that predominantly inactive rDNA repeats are associated with the nuclear matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Then enzymatic ligation of DNA fragments held in proximity is carried out followed by identification of such fragments by different means. So far only a single study of 3C applied to preparations extracted for NM, hence devoid of chromatin proteins (M3C), has been published and the results showed that important DNA sequences labeled as proximal to each other in the standard 3C protocol were not so in the M3C assay [Gavrilov et al, 2010]. Yet despite its uncertainties many a scientist infer that a DNA loop exists between two DNA sequences positive in the artificial proximity ligation procedure of 3C.…”
Section: Discussionmentioning
confidence: 99%